2018
DOI: 10.3390/environments5060072
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Used Tyre Rubber by Pyrolysis: Enhancement of the Physical Properties of the Liquid Fraction Using a Hydrogen Stream

Abstract: Abstract:The disposal of discarded tyres represents an environmental challenge for solid waste management entities. The need to reduce solid waste in urban areas along with the depletion of natural resources have made it necessary to reincorporate used materials into productive processes, giving value to what is considered waste, and minimizing the requirement of natural resources. In this study, pyrolysis was selected to thermally decompose used ground waste vulcanized rubber from automobile tyres. This rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
(32 reference statements)
2
28
0
2
Order By: Relevance
“…In contrast to direct combustion, however, it is possible to control the pyrolysis process within some limits. The authors of [8] determined that the temperature of the process affects rubber decomposition and, respectively, pyrolysis products. Raising the temperature above 500 • C contributed to the production of liquid and gas fractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to direct combustion, however, it is possible to control the pyrolysis process within some limits. The authors of [8] determined that the temperature of the process affects rubber decomposition and, respectively, pyrolysis products. Raising the temperature above 500 • C contributed to the production of liquid and gas fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a large proportion of ELTs consists of organic compounds and can be considered as an energy resource. Differences in heat treatment and in gas atmosphere during pyrolysis lead to a different degradation pathway for the rubber [8]. One can obtain a larger or smaller quota of gases, liquid product, and pyrocarbon.…”
Section: Introductionmentioning
confidence: 99%
“…Banihani et al [27] adopted the thermal pyrolysis method of waste tyre in presence of catalyst to prepare oil in which the effect of catalysts and their ratio on the pyrolysis product oil is investigated and found that the maximum liquid yield obtained from pyrolysis of waste tyre with catalyst like activated alumina and zeolite as 49.32% and 51.54% compared to 42.48% without catalyst. Ramirez-Canon et al [28] analyzed the effect of liquid fraction of TPO on environment and found that the presence of hydrogen stream improves the appearance of fuel and also reduces the sulphur content, water and sediments and increases the heating capacity of fuel.…”
Section: Pyrolysis-oil Conversion Process For Tyrementioning
confidence: 99%
“…Одним из наиболее эффективных способов переработки вторичного сырья с целью получения жидкого топлива является пиролиз. Продукты пиролиза могут быть использованы в качестве ценных углеводородов или углеводородного топлива [1][2][3]. Анализ Химического состава жидкого пиролизата важен как для оценки степени его токсичности, так и для поиска эффективного способа его очистки и дальнейшего использования в качестве топлива.…”
Section: Introductionunclassified